A Review of Smooth Variable Structure Filters: Recent Advances in Theory and Applications - Gadsden SA; Afshari HH (ASME International, 2015)
The smooth variable structure filter (SVSF) is a relatively new state and parameter estimation technique. Introduced in 2007, it is based on the sliding mode concept, and is formulated in a predictor-corrector fashion. The main advantages of the SVSF, over other estimation methods, are robustness to modeling errors and uncertainties, and its ability to detect system changes. Recent developments have looked at improving the SVSF from its original form. This review paper provides an overview of the SVSF, and summarizes the main advances in its theory.
Keywords: 4901 Applied Mathematics; 40 Engineering; 49 Mathematical Sciences